Chaotic dynamics and some solutions for the (n + 1)-dimensional modified Zakharov–Kuznetsov equation in plasma physics - Zhao Shan; Feng Jun (Open Physics)
In the ongoing work, the (n+1n+1)-dimensional modified Zakharov–Kuznetsov equation is discussed, which characterizes the dispersive and ion acoustic wave propagation in plasma physics. The main research content is to analyze the chaotic dynamics of the equation and provide some new traveling wave solutions. The studied equation is transformed into an ordinary differential equation by using traveling wave transformation. The bifurcation theory, Lyapunov exponent, and sensitivity of initial value condition are employed to analyze the chaotic behavior and stability of the equation. Furthermore, by utilizing the integral form of the equation and complete discrimination system for polynomial method, some new exact solutions are given, including rational, trigonometric, hyperbolic, and Jacobi elliptic function solutions. To examine the properties and shapes of the solutions, some two- and three-dimensional graphs are given with the aid of MATLAB software under appropriate parameters intuitively.